Impact of Autophagy on Chemotherapy and Radiotherapy Mediated Tumor Cytotoxicity: “To Live or not to Live” - Zeng, Xuehuo; Kinsella, Timothy J. (Frontiers in Oncology, 2011)
Autophagy, a highly regulated cell "self-eating" pathway, is controlled by the action of over 34 autophagy-related proteins (collectively termed Atgs). Although they are fundamentally different processes, autophagy and apoptosis (type I programmed cell death), under certain circumstances, can be regulated by common signaling mediators. Current cancer therapies including chemotherapy and ionizing radiation are known to induce autophagy within tumor cells. However, autophagy plays a dual role of either pro-cell survival or pro-cell death in response to these cancer treatments, depending on the cellular context and the nature of the treatment. We review the current basic and translational cancer research literature on how autophagy impacts tumor cell survival (“to live”) and death (“not to live”) following treatment as well as the role of chemical mediators of autophagy.